Development of Augmented Reality-Based Adaptive Media to Stimulate Student Engagement in Pancasila Education for Third-Grade Elementary School Students - Komang Vera Pebrianti; Putu Aditya Antara; Ketut Susiani (Universitas Pendidikan Ganesha, 2026)
Low student engagement in Pancasila Education learning remains a challenge in creating meaningful learning experiences for elementary school students. Therefore, this study aims to develop and examine the effectiveness of adaptive learning media based on augmented reality in stimulating students’ engagement in the topic “Aku Anak Indonesia.” This study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects involved third-grade elementary school students. Data were collected through expert validation questionnaires, practicality questionnaires, and student engagement measurement instruments. The data were analyzed using descriptive quantitative analysis and hypothesis testing to determine the effectiveness of the developed media. The results showed that the augmented realitybased adaptive learning media met the criteria of validity based on evaluations by media and content experts and was considered practical based on user responses. Furthermore, the findings indicated that the use of the media was effective in increasing students’ engagement during the learning process. Thus, it can be concluded that augmented reality based adaptive media is a valid, practical, and effective learning tool for stimulating students’ engagement in Pancasila Education learning. The implications of this study indicate that the integration of augmented reality technology in adaptive learning media can serve as an innovative alternative strategy for teachers to create more interactive, contextual, and meaningful learning experiences that align with students’ learning characteristics in the digital era.